L’identité littéraire franco-allemande de Heinrich Mann : entre projection de soi et réalité - Frédéric Teinturier (Recherches Germaniques)
This article presents a synthetic analysis of the use of the French language in Heinrich Mann’s work. The author’s cultural identity was strongly influenced by France and French literature. Furthermore, he had excellent language skills in French, which made it possible for him to translate some French novels into German and to have a rich correspondence with French friends; he managed also to write many essays as well as cultural and political articles in French during the first phase of his exile. Nevertheless, he never wrote fiction directly in French. Heinrich Mann’s cultural identity between France and Germany is an exceptional case, which reveals both the complexity and the contradictions of his intellectual career.